The fury ebook - Michaelides, Alex (2024)
**THE INSTANT NEW YORK TIMES BESTSELLER** "Alex Michaelides hits the trifecta with his third novel, The Fury . The highly original story presents the reader with the king of all unreliable narrators, enough twists and turns to power two novels, and a host of characters that bleed right on the page. " —David Baldacci A masterfully paced thriller about a reclusive ex–movie star and her famous friends whose spontaneous trip to a private Greek island is upended by a murder — from the #1 New York Times bestselling author of The Silent Patient This is a tale of murder. Or maybe that's not quite true. At its heart, it's a love story, isn't it? Lana Farrar is a reclusive ex–movie star and one of the most famous women in the world. Every year, she invites her closest friends to escape the English weather and spend Easter on her idyllic private Greek island. I tell you this because you may think you know this story. You probably read about it at the time ― it caused a real stir in the tabloids, if you remember. It had all the necessary ingredients for a press sensation: a celebrity; a private island cut off by the wind...and a murder. We found ourselves trapped there overnight. Our old friendships concealed hatred and a desire for revenge. What followed was a game of cat and mouse ― a battle of wits, full of twists and turns, building to an unforgettable climax. The night ended in violence and death, as one of us was found murdered. But who am I? My name is Elliot Chase, and I'm going to tell you a story unlike any you've ever heard.